2022
DOI: 10.1021/acsami.2c00398
|View full text |Cite
|
Sign up to set email alerts
|

Strained Pt(221) Facet in a PtCo@Pt-Rich Catalyst Boosts Oxygen Reduction and Hydrogen Evolution Activity

Abstract: Over the last years, the development of highly active and durable Pt-based electrocatalysts has been identified as the main target for a large-scale industrial application of fuel cells. In this work, we make a significant step ahead in this direction by preparing a high-performance electrocatalyst and suggesting new structure−activity design concepts which could shape the future of oxygen reduction reaction (ORR) catalyst design. For this, we present a new onedimensional nanowire catalyst consisting of a L1 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 51 publications
0
28
0
Order By: Relevance
“…Hydrogen has the potential to replace conventional energy carriers as a sustainable green energy source. , One promising method of hydrogen production is the electrochemical water-splitting process, given that the energy required, i.e., reaction overpotential, is reduced to an acceptable level. , In order to accomplish that, there is a need for the development of highly efficient and cost-effective electrocatalysts to improve the energy efficiency of the hydrogen evolution reaction (HER) process. , Currently, the most efficient HER electrocatalysts are platinum-based electrodes, but their use in practical applications is limited by the high cost and scarcity of resources. Recent research for practical and efficient non-noble metal-based catalysts revealed that some of the transition metals, such as Ni, Mo, W, and Co in the form of oxides, sulfides, phosphides, selenides, , and carbides, have shown promising catalytic activity toward hydrogen evolution and are highly stable in alkaline electrolytes. These transition metals are some of the most earth-abundant materials and are cost-effective, making them more appealing compared to noble metals.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen has the potential to replace conventional energy carriers as a sustainable green energy source. , One promising method of hydrogen production is the electrochemical water-splitting process, given that the energy required, i.e., reaction overpotential, is reduced to an acceptable level. , In order to accomplish that, there is a need for the development of highly efficient and cost-effective electrocatalysts to improve the energy efficiency of the hydrogen evolution reaction (HER) process. , Currently, the most efficient HER electrocatalysts are platinum-based electrodes, but their use in practical applications is limited by the high cost and scarcity of resources. Recent research for practical and efficient non-noble metal-based catalysts revealed that some of the transition metals, such as Ni, Mo, W, and Co in the form of oxides, sulfides, phosphides, selenides, , and carbides, have shown promising catalytic activity toward hydrogen evolution and are highly stable in alkaline electrolytes. These transition metals are some of the most earth-abundant materials and are cost-effective, making them more appealing compared to noble metals.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of lattice fringes indicates that PtCo NPs were highly crystalline in PtCo/NPC-Co. The lattice fringes measured to 0.221 nm (Figure S3), corresponding to the crystal lattice face of the (111) planes of Pt, were smaller than those of pure Pt (0.227 nm), attributable to lattice shrinkage . The phenomenon further proved the formation of PtCo alloy.…”
Section: Resultsmentioning
confidence: 89%
“…41 The diffraction peaks of the prepared catalysts exhibit higher intensity than that of pure Pt, demonstrating lattice shrinkage caused by the entry of smaller Co atoms into the Pt crystal lattice, which resulted in the formation of PtCo alloy NPs. 42 TEM and SEM tests were performed to characterize the morphology of NPC and NPC-Co. NPC (Figure 3a,b) and NPC-Co (Figure 3d,e) have similar morphologies and interconnected hierarchical porous structures. The formation of the mesopore and macropore structures arises from removing ZnO and Co templates, which increases the specific surface area of carbon materials.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, neutral-pH water electrolysis receives growing attention and is proposed to generate H 2 recently because of the gentle handling environment and extended device lifetime . The derived application of water electrolysis in real seawater also contributes to recent research endeavors on water electrolysis at neutral pH. However, the development of nonacidic water electrolysis confronts the issue of limited current density due to the sluggish kinetics of the water dissociation step …”
Section: Introductionmentioning
confidence: 99%
“…Nonprecious transition-metal-based materials have been extensively explored due to the balanced HER performance and cost, such as transition metal/alloys, , chalcogenides, phosphides, and carbides. Though some catalysts show better HER activity than the state-of-the-art Pt/C catalyst in alkaline media, the unstable structure and deteriorative HER performance are also observed during long-term stability measurements. , Moreover, strict and harsh conditions are required for the preparation of these active catalysts, e.g., toxic and corrosive PH 3 for phosphides and extremely high temperatures for carbides. , Green and scaled-up syntheses of highly efficient catalysts are in demand for industrial-scale water electrolysis.…”
Section: Introductionmentioning
confidence: 99%